Website-Based Information System Design for Audio Car Service Administration Management at PT. Berkat Audio Perkasa Jaya - Putri, Farazayu Nanda; Ramos, Samuel; Sudarsono, Bernadus Gunawan (Journal of Engineering, Technology and Computing (JETCom), 2025)
PT Berkat Audio Perkasa Jaya is a company engaged in car audio installation services. The administrative process is still done manually, including customer registration, scheduling, and financial reporting, causing delays and data errors. Therefore, this study aims to design a website-based information system to manage car audio service administration. The methods used include observation, interviews, and literature review. The system is designed using UML modeling and developed using PHP and MySQL. The results show that the developed system can automate administrative processes, increase efficiency, and support real-time decision-making.